The town mouse and the country mouse - Davidson, Susanna; Aesop; East, Jacqueline (London : Usborne ; Tulsa, Okla. : EDC, 2007)
When the town mouse and the country mouse visit each other, they find they prefer very different ways of life.
"Based on a story by Aesop."
"Level four"--Cover p. [4].
2.1
K-3.
K-3
Keywords: Fables; Mice -- Folklore; Fables; Mice -- Folklore